Environmental and Social Impacts of Chinese Infrastructure Development in East Africa - Roque de Pinho, Joana (The Silk Roads Conference – Anticipating Social and Environmental Impacts of China’s Belt and Road Initiative in the Mountains of Central Asia, 2018)
2018. Roque de Pinho, J. Environmental and Social Impacts of Chinese Infrastructure Development in East Africa, “Silk Roads Conference – Anticipating Social and Environmental Impacts of China’s Belt and Road Initiative in the Mountains of Central Asia”, Mountain Societies Research Institute, University of Central Asia (UCA), Bishkek, Kyrgyzstan (October 26th, 2018).